Research on the automatic generation code for nuclear fuel reloading patterns in pressurized water-cooled reactors - Abednego Kristanto; Wang Kan; Peng Sitao (Journal of Engineering and Applied Technology, 2021)
A method for automated generation program for nuclear fuel reloading patterns in Pressurized Water Reactor (PWR) has been developed. This newly-developed method consists of six different steps to minimize the maximum FΔH value, and maximize the reactor cycle length. Step 1 is initial fuel placement that is expected to produce the longest cycle length possible with the selected Fuel Assemblies (FAs) for the current cycle. Step 2 is aiming to decrease the FΔH value of the FA with the maximum FΔH. Step 3 aims to increase the FΔH value of the old FA with the lowest FΔH. Step 4 is rotating FA with the lowest FΔH value to increase its FΔH value, and rotating several old FAs in the neighboring FA with the maximum FΔH value to decrease the maximum FΔH value. Step 5 is aiming to increase the FΔH value of FA with the lowest FΔH value. The last step or step 6, will try to move FAs that have high k∞ in the periphery zone, inward to increase the cycle length of the reactor. These steps are translated into code in the Python programming language to enable automatic execution in a computer. A 3D nuclear reactor core neutronic code, COCO, is used for the calculation of FΔH value and reactor cycle length. Every nuclear power plant designer company will have their FΔH peaking factor safety limit in accordance with their DNB experiments and calculations, and the FΔH value safety limit used in this research is 1.46. A PWR loading pattern model is used to test this method. During the test, all the steps in this method are successfully executed in a total of 25 iterations plus one initialization calculation and produced acceptable results. The results of this method are all of the loading patterns found in all steps which have the maximum FΔH value below the defined criterion values. In the mentioned PWR loading pattern model, four optimized loading patterns are found using this method, all of which can be selected in the PWR refueling loading pattern design.